The Dreyfus affair the story of the most infamous miscarriage of justice in French history - Read, Piers Paul 1941- (Bloomsbury, 2012)
In October 1894, the torn fragments of an unsigned memo containing military secrets were retrieved by a cleaning lady from the waste paper basket of Colonel Maximilien von Schwartzkoppen of the German embassy in Paris. When French intelligence pieced the document back together to uncover proof of a spy in their midst, Captain Dreyfus, on slender evidence, was charged with selling military secrets to the Germans, found guilty of treason by unanimous verdict and sentenced to life imprisonment on the notorious Devi' s Island. The fight to free the wrongfully convicted Dreyfus - over twelve long years, through many trials - is a story rife with heroes and villains, courage and cowardice, dissimulation and deceit. One of the most infamous miscarriages of justice in history, the Dreyfus affair divided France, stunned the world and unleashed violent hatreds and anti-Semitic passions which offered a foretaste of what was to play out in the long, bloody twentieth century to come
Includes bibliographical references and index
Keywords: Dreyfus, Alfred / 1859-1935 / Trials, litigation, etc; Geschichte 1800-1900; Geschichte 1870-1940; Trials (Treason) / France / History / 19th century; Judicial error / France / History / 19th century; Antisemitism / France / History / 19th century; Antisemitismus; Geschichte; Dreyfusaffäre; Justizirrtum; France / History / Third Republic, 1870-1940; Frankreich